2016
DOI: 10.1364/boe.7.003826
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of extra-cerebral and cerebral hemoglobin concentrations during physical exercise using time-domain near infrared spectroscopy

Abstract: Fitness is known to have beneficial effects on brain anatomy and function. However, the understanding of mechanisms underlying immediate and long-term neurophysiological changes due to exercise is currently incomplete due to the lack of tools to investigate brain function during physical activity. In this study, we used time-domain near infrared spectroscopy (TD-NIRS) to quantify and discriminate extra-cerebral and cerebral hemoglobin concentrations and oxygen saturation () in young adults at rest and during i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 69 publications
3
33
0
Order By: Relevance
“…Regarding decreased HHb concentrations, these findings are reasonable and can be explained by previous studies demonstrating that more complex movements are associated with cortical activation increases in SMA and adjacent premotor areas (Orgogozo and Larsen 1979). Even though cortical processing during a rhythmic alternating activity such as cycling has mainly been investigated in prefrontal brain regions by means of fNIRS (Auger et al 2016; Giles et al 2014; Rupp et al 2008), recent studies pointed to the important role of motor-related brain regions in cycling. For example, using PET, Christensen et al (2000) observed an activation in M1 and SMA during active and passive cycling as two conditions of a rhythmic alternating activity in leg muscles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding decreased HHb concentrations, these findings are reasonable and can be explained by previous studies demonstrating that more complex movements are associated with cortical activation increases in SMA and adjacent premotor areas (Orgogozo and Larsen 1979). Even though cortical processing during a rhythmic alternating activity such as cycling has mainly been investigated in prefrontal brain regions by means of fNIRS (Auger et al 2016; Giles et al 2014; Rupp et al 2008), recent studies pointed to the important role of motor-related brain regions in cycling. For example, using PET, Christensen et al (2000) observed an activation in M1 and SMA during active and passive cycling as two conditions of a rhythmic alternating activity in leg muscles.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were confirmed in fNIRS studies showing increased oxygenation (Takehara et al 2017) and deoxygenation (Jung et al 2015) with elevating exercise intensities. Furthermore, previous studies revealed exercise-induced activations in prefrontal cortex (PFC) showing that Hb and HHb levels respond as a function of both exercise load and duration in both experts (Rupp et al 2008) and non-experts (Auger et al 2016; Giles et al 2014; Jung et al 2015). However, previous studies focusing on neurovascular coupling at several intensity levels show that there is no consensus concerning the type of exercise (incremental tests with short stages vs. constant-load exercises), duration of exercise (Giles et al 2014; Tsubaki et al 2016) and intensity (Auger et al 2016; Byun et al 2014; Giles et al 2014; Takehara et al 2017; Tsubaki et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The distance-resolved NIRS technique may allow to reduce such extracerebral contamination [8,9], however the time-resolved near infrared spectroscopy (trNIRS) technique still remains the most advanced approach. The trNIRS allows to gather more information about the tissue of interest, in comparison to cwNIRS technique [10][11][12]. It was reported that trNIRS allows to estimate optical properties of the tissue (absorption and reduced scattering coefficients µ a and µ s ') considered as a homogenous medium [13].…”
Section: Introductionmentioning
confidence: 99%
“…Although here we computed EAC values in healthy adults, an important application of EAC mapping would be to investigate people with pathological conditions that affect both oxygenation and anatomy (e.g., superficial hemorrhages, strokes, etc. ), or where subtle, regional and perhaps temporary physiological [71] or pathological alterations of oxygenation (such as concussion [72]) are suspected. In fact, in this paper we only considered the generation of static EAC maps (i.e., the average maps across the recording period) to maximize SNR.…”
Section: Discussionmentioning
confidence: 99%